The Demand for Currency Substitution - John J. Seater (Kiel Institute for the World Economy (IfW), 2008)
A transactions model of the demand for multiple media of exchange is developed. Some results are expected, and others are both new and surprising. There are both extensive and intensive margins to currency substitution, and inflation may affect the two margins differently, leading to subtle incentives to adopt or abandon a substitute currency. Variables not previously considered in the literature affect currency substitution in complex and somewhat unexpected ways. In particular, the level of income and the composition of consumption expenditures are important, and they interact with the other variables in the model. Independent empirical work provides support for the theory.
Keywords: E41; E42; E31; 330; Currency substitution; Dollarization